Workers in the Small and Medium Industry Sector in the Anak Air Health Center Working Area: Instruction and Training on Proper Nutrition - Zurni Nurman; Made Dewi Sariyani (CV. Get Press Indonesia, 2024)
Nutrition training programmes for small and medium enterprises (SMEs) have great potential to improve the welfare and productivity of the workforce. This study used mixed methods research with quantitative and qualitative approaches. A total of 120 workers in the SME sector in the Anak Air health centre working area were selected as the research sample. Data were collected through a questionnaire designed based on relevant nutrition indicators, such as diet, frequency of consumption of nutritious food, and health status of workers. The quantitative data were analysed using descriptive statistical tests to describe the distribution of baseline data, as well as inferential tests to assess significant differences between pre- and post-training intervention outcomes. Qualitative in-depth interviews and focus group discussions (FGDs) were conducted to gain an indepth understanding of workers' perceptions, challenges faced, and recommendations for programme development. The results showed that the nutrition training had a significant impact on improving the knowledge, attitudes, and behaviours of workers related to healthy nutrition after attending the training. When food and macronutrient availability is closer to the proportion of healthy consumption patterns, there is a possibility of reducing stunting in the neighbourhood.